Effect of ethylene co-feeding in Fischer-Tropsch synthesis: A study of reaction equilibrium and competition. (15th October 2021) - Zhang, Yusheng; Yao, Yali; Shen, Jianqi; Chang, Jianli; Gorimbo, Joshua; Liu, Xinying; Hildebrandt, Diane
Graphical abstract: Highlights: Competitive Reaction Equilibrium may be explained the FT-type product distribution. The ratio of Pn /On varied with different feed mixtures and operating temperatures. A linear relationship of Pn+1 /On+1 vs. Pn /On (n > 2) holds for a wide range of conditions. Yao plots could also be applied to non typical FTS. The gradient of P3 /O3 vs. P2 /O2 decreased with increasing the amount of C2 H4 . Abstract: The effect of both C2 H4 and CO's partial pressures as co-feeds on the paraffin to olefin (P/O) ratio during Fischer − Tropsch synthesis (FTS) over a 15 wt% Co/TiO2 catalyst was investigated. The P/O ratio was also affected by the process conditions and different trends were observed at relatively low temperatures (<200 °C) and high temperatures (>200 °C). These observations were attributed to the nature of the interaction between different chain-growth mechanisms. The product distribution was presented using graphically using "Yao plot" (Pn+1 /On+1 vs. Pn /On ). Although the P/O ratio varied at different conditions, a phenomenal linear relationship between Pn+1 /On+1 and Pn /On (n > 2) was obtained. The gradients were in a narrow range, which was consistent with the result obtained on normal FTS. This indicated that this linear relationship is universal. A new "competitive reaction equilibrium" was proposed to explain these observations.